Pandangan Kiai tentang Deradikalisasi Paham Islam Radikal di Kota Semarang - Abu Rokhmad (Analisa: Journal of Social Science and Religion, 2014)
AbstractThe face of Islamic moderate in Indonesia changed since the decline of new era regime in 1998. Hardliner moslem communities grew in society. They didn’t embarrassed to use  violent ways, even terorism. Nowadays radicalism isthe most important problems faced bythe moslem society in Indonesia. The participation of kiai was badly needed to handle radicalism problems. This article studies the views of kiai about the roots of Islamic radicalsm and the strategies of kiai to deradicalize Islamic radicalism. The conclusion of this article were: first, the root of radicalism becaused of two factors: religius factor thatis literal understanding or misunderstanding of religious texts, and the political factor related to national and global issues. Second, there were two forms of deradicalization, related to the characteristics of the subject of radicalism: preventive deradicalization and curative deradicalization.Keywords: islamic radicalism, radicalism, deradicalization, kiai. AbstrakWajah Islam moderat di Indonesia kian berubah sejak rezim Orde Baru tumbang pada 1998. Kelompok-kelompok Muslim garis keras tumbuh subur di masyarakat. Mereka tidak segan berdakwah dengan cara kekerasan bahkan terorisme. Radikalisme menjadi masalah penting bagi umat Islam Indonesia dewasa ini. Keterlibatan kiaidalam menangani masalah radikalisme (deradikalisasi) sangat diharapkan. Artikel ini mengkaji dua hal. Pertama, bagaimana pandangan kiai tentang akar radikalisme Islam? dan Kedua, bagaimana strategi kiai dalam melakukan deradikalisasi pahamIslam radikal? Kesimpulan artikel ini adalah: Pertama, akar radikalisme disebabkan dua faktor besar, yaikni faktor pemahaman agama yang kurang tepat dan faktor politik yang berhubungan isu nasional dan global. Kedua,terdapat dua model deradikalisasi, tergantung sifat dari pelaku radikalisme: deradikalisasi pencegahan (preventive deradicalization), dan deradikalisasi penyembuhan (curative deradicalization).Kata kunci: Islam Radikal, Radikalisme, Deradikalisasi, Pesantren, Kiai.